Experimental Plot of Durum Wheat under Conservation Agriculture/No-Till – El Rhahala Region, Siliana District, Tunisian Agroecological Living Landscape - Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2022)
Experimental Plot of Durum Wheat under Conservation Agriculture/No-Till – El Rhahala Region, Siliana District, Tunisian Agroecological Living Landscape.